2023
DOI: 10.1037/rmh0000237
|View full text |Cite
|
Sign up to set email alerts
|

In their own voice: Behavioral health care delivery barriers in rural New York.

Brett R. Harris,
Katie C. Gallant

Abstract: Rural areas are disproportionately impacted by mental health and substance use disorders, drug overdose, and suicide. Several environmental and service access barriers are linked to these disparities, yet little is known about facilitators and barriers to care delivery that may impact client outcomes. Our study sought to explore these facilitators and barriers from the perspective of service providers. We conducted a qualitative focus group study with 206 professionals with a vested interest in behavioral heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…These findings of disproportionality are global, with similar observations made in countries in Africa, Australia, and North America. [21][22][23] In a study surveying farmers from Ontario, Canada, farmers indicated both geography and culture were significant barriers and felt that even when mental health practitioners were utilized, there was often a disconnect between providers and their understanding of the culture of farming, leading to a lack of "farm credibility." 24 Interventions to address farmer suicide risk and mental health are limited.…”
Section: Introductionmentioning
confidence: 99%
“…These findings of disproportionality are global, with similar observations made in countries in Africa, Australia, and North America. [21][22][23] In a study surveying farmers from Ontario, Canada, farmers indicated both geography and culture were significant barriers and felt that even when mental health practitioners were utilized, there was often a disconnect between providers and their understanding of the culture of farming, leading to a lack of "farm credibility." 24 Interventions to address farmer suicide risk and mental health are limited.…”
Section: Introductionmentioning
confidence: 99%